(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The desolation of Wuhan’s empty roads will always mark the memory of the last days of 2019. Epidemics and pandemics, indeed, determine a restrictive impact on the freedoms of movements, for both individuals and trade. Research is a different story: the circulation of the knowledge and the results it produces, and of biological materials too, should be encouraged. The purpose of this study is to explore States’ duties under international law in the field of research, in times of health emergencies, in order to advance some critical considerations in relation to the challenges that CoViD-19 poses for the international community.